GWO based controller design for Riverol-Pilipovik water treatment plant. Issue 2 (17th February 2020) - Chodavarapu, Madan Mohan; Shaw, Binod; Singh, Vinay Pratap
Abstract: In this work, grey wolf optimization (GWO) based controller design is proposed for Riverol-Pilipovik (RP) water treatment system. The RP water treatment system considered in this work is basically an interacting two-input-two-output (TITO) system. The interacting TITO system is first converted into two non-interacting loops by designing decoupler. For the obtained non-interacting loops, two separate proportional-integral-derivative (PID) controllers should be designed by minimizing the integral-of-squared-error (ISE). Constructed ISE is minimized using recently proposed GWO algorithm. For showing the efficiency of GWO assisted controllers, two test cases are considered in this work. The results obtained show that GWO based PID controllers are excellent in performance.